KEBERADAAN ASAS PRADUGA TAK BERSALAH PADA PROSES PERADILAN PIDANA : KAJIAN - Nurhasan Nurhasan (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The principle of presumption of innocence is the most basic principal in determining a person's guilt or innocence in a judicial process that guarantees of human rightsmaintained and protected, then it is interesting to see how the existence of the principle of presumption of innocence in the criminal justice system and dependencieswith human rights. The purpose of this research was: 1) in order to know and understand the basic settings of the existence of presumption of innocence in the criminal justice system. 2) to know and explain the relationship of the principle of presumption of innocence with human rights. The meaning implied in the protection and recognition of the principle of presumption of innocence, is a very important element ofmeaning and purpose in order to uphold and respect towards the rights of a person. The principle of presumption of innocence that is the embodiment of human rights which guarantee the protection of the rights of the suspect or the accused in thecriminal justice process.Keyword: the principle of presumption of innocence, human rights, criminal justice